Jesus in the Talmud - Schäfer, Peter, 1943- (Princeton University Press, 2007)
Scattered throughout the Talmud, the founding document of rabbinic Judaism in late antiquity, can be found quite a few references to Jesus--and they're not flattering. In this lucid, richly detailed, and accessible book, Peter Schäfer examines how the rabbis of the Talmud read, understood, and used the New Testament Jesus narrative to assert, ultimately, Judaism's superiority over Christianity. The Talmudic stories make fun of Jesus' birth from a virgin, fervently contest his claim to be the Messiah and Son of God, and maintain that he was rightfully executed as a blasphemer and idolater. They.